Friday

March 6, 2015

March 6, 2015

Posted by **Hannah** on Sunday, February 27, 2011 at 8:07pm.

g(x)=(x^3+1)(3x^2-1)

I know that the answer is

15x^4-3x^2+6x but I donot know how to get to this. I was using

g'(x) X h(x) + g(x) X h'(x) and I was using the derivatives 3x^2 and 6x but I guess this is wrong. Please help!! Thank you.

- Math(Urgent) -
**Reiny**, Sunday, February 27, 2011 at 8:18pmg '(x) = 6x(x^3+1) + 3x^2(3x^2-1)

= 6x^4 + 6x + 9x^4 - 3x^2

= 15x^4 - 3x^2 + 6x

- Math(Urgent) -
**Hannah**, Sunday, February 27, 2011 at 8:40pmThank You

**Answer this Question**

**Related Questions**

Algebra - I need help trying to put the correct vocabulary words when solving ...

Maths - Differentiate using the product rule. How do i get from dy/dx = d(uv)/dx...

Algebra - I need help trying to put the correct vocabulary words when solving ...

Calculus - I'm having problems with this one. Can't get the right answer. ...

math - If cos(3 x)−4 x e^2 y=0, find [ dy/dx] using implicit differentiation...

calculus - derivatives differentiate y=x^7/3 So far I have Y=7/3X Is this all ...

math - Express y=[4x-x^3]/[3x^2+2)^2 as a product and then differentiate. ...

math - can some one please help me with the following questions as i dont ...

Physics(Urgent) - Using Planck's constant as h=6.63 E-34 J*s, what is the ...

ALGEBRA! URGENT. Check Answers! - 1. 18x^2 + 6 + 4x - 15x^2 - 4 + 13x Answer: 3x...